Effects of Accounting Information, Financial Literacy and Risk Perception on Student Investment Decisions - Ghania Callysta Firstikara; Firman Hidayat (Interdisciplinary Social Studies, 2026)
This research is motivated by a paradoxical phenomenon in which only 5.46% of students from the Faculty of Economics and Business (FEB), Universitas Swadaya Gunung Jati Cirebon, participate in investment activities, far below the national average of young investors at 54.62%, despite having adequate theoretical investment knowledge. This study aims to analyze the influence of accounting information, financial literacy, and risk perception on FEB students’ investment decision-making to explain the gap between theory and practice. The novelty of this research lies in its focus on FEB students with formal economic education and the integration of accounting information, financial literacy, and risk perception within the Theory of Planned Behavior framework in a regional university context. This study employed a causal-associative quantitative approach involving 100 active students selected through purposive sampling. Primary data were collected using a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that accounting information has a significant positive and dominant effect on investment decisions (? = 0.512), while risk perception also has a significant positive influence (? = 0.258). In contrast, financial literacy does not have a significant effect (? = ?0.061). Collectively, these variables explain 38.7% of the variance in students’ investment decisions. The findings indicate that the ability to analyze accounting information and manage risk perception is more decisive in investment decision-making than theoretical financial literacy. Therefore, strengthening financial statement analysis skills and integrating financial analysis and risk management practicum are recommended to increase students’ investment participation.